A cross segments examination of using neural networks for stock picking on Wall Street - Tan, Shi Wei. (2009)
This report is to indicate the knowledge gathered by the project participants through the course of the project and to demonstrate the experimentation that has been conducted, the results of the experiments as well as the problems encountered and ways of improvements for this project in a clear and distinct manner. The report will break down into three sections as follows: 1. INTRODUCTION & OBJECTIVE 2. LITERATURE REVIEWS 3. EXPERIMENTATION PROCESS 4. RESULTS & CONCLUSION 5. PROBLEMS ENCOUNTERED AND SOLUTIONS 6. WAYS OF IMPROVEMENTS 7. KNOWLEDGE ACQUIRED FROM THIS PROJECT 8. APPENDIXES 9. REFERENCES For the first section, the basis behind the project and the reason of proceeding with the project will be clearly defined. This will be followed by providing backgrounds on the two essential elements that will affect the outcome of the project:  Artificial Neural Network  Wall Street and Market Analysis Next, the report will cover the experimentation process as well as the results that were obtained, which will followed by a clear description of some of the difficulties encountered through the course of the project. Finally, the report will conclude with suggestions on some ways of improvements as well as some subjective thoughts on what the participant has learnt and benefited from partaking in this project.